Architecture on the Moon: Expanding the boundaries of Space - Андрей Кафтанов (Проект Байкал)
The article examines the peculiarities of Soviet modernism of the 1960s – 1980s aimed at the spatial development of the country. The history of space exploration and attempts to conquer the Moon are also included in these processes. The article presents the projects of Russian architects who worked in that period for the lunar exploration programmes. It also reveals details of the real project of the Lunar Base, which was carried out by architect Igor Kozlov from 1970 to 1980.